JENIS-JENIS TUMBUHAN OBAT YANG DIGUNAKAN MASYARAKAT DESA INDURIANG KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Riyandi, Rahmat; Nursyahra, Nursyahra; Rizki, Rizki (STKIP PGRI Sumbar, 2013)
ABSTRACTAlmost all people in the Induriang village use traditional medicinal plants, whether plants that have been cultivated and wild growing plants. This study was conducted to determine the types of medicinal plants used by people in the Induriang village. The research was conducted in June 2013 by a descriptive survey method, the sampling in the village Induriang researchers assisted by 2 shaman and sampling carried out in the fields, houses and woods around the radius depth of ± 100 meters from the road. From this study, it was found as many as 33 species of medicinal plants from 22 familia and can be used to treat 28 kinds of diseases outside and internal medicine. Medicinal plant species most commonly found are from Familia Poaceae, Myrtaceae, Euphorbiaceae and Zingiberaceae respectively 3 types and is advisable to be able to conduct further research on the ecology of medicinal plants that exist in the area.